Clinical experience with a simple retraction device in single-port laparoscopic cholecystectomy: Technical description and initial results. Issue 3 (June 2014) - Dauser, Bernhard; Ghaffari, Shahbaz; Herbst, Friedrich
Abstract Background: Performing single-port laparoscopic cholecystectomy (SPLC) is challenging as triangulation is limited and the critical view is difficult to obtain. We present our initial experience using a simple retraction device to reduce these problems. Material and methods: In January 2012 a novel lifter was introduced at our department and subsequently used in SPLC for suspension of the gallbladder. Perioperative data were collected prospectively. In addition, all videos were reviewed to assess any adverse events caused by the lifter. Results: Thirty (20 female and 10 male) patients at a median age of 48.4 years (range: 23–83) were operated using this novel retraction device. Median BMI accounted for 26.0 kg/m2 (median; range: 14.0–36.9). Retraction of the gallbladder using the lifter was possible in all patients. In four cases (13.3 %) spillage of bile caused by the lifter was recorded. In addition, perforation of the gallbladder was seen once (3.3 %), caused by electrocautery. No inflammation, induration or visible scars were seen in the right upper quadrant at six weeks postoperatively in any patient. Conclusions: Gallbladder retraction in SPLC using this novel device is feasible and safe without leaving any apparent scar. Rate of bile spillage is (at least) comparable to that reported for conventional laparoscopic cholecystectomy.